Research on rail and maritime transport interoperability in the area of information systems: the case of Lithuania - Jarašūnienė, Aldona; Čižiūnienė, Kristina; Petraška, Artūras (Transport, 2019)
With the acceleration of globalization processes and increased international cooperation, freight transport routes are expanding, which requires new solutions for the most efficient use of various modes of transport. One of the most important factors that may improve the efficiency of the interoperability of different transport modes is information exchange allowing to plan transport flows in advance, exploiting benefits of the maritime and rail transport and minimizing its disadvantages. Precise information allows to find the most efficient mode of transport for the freight transportation chain. Precise information is necessary for effective management of information flows to ensure interoperability between the transport modes. This article analyses the specificity of railway and maritime transport modes, hence research questionnaire of Lithuanian transport companies is performed to present the results to show the most significant elements of railway and maritime transport interoperability. The completed expert evaluation enabled to prioritize the sequence of elements to ensure the efficient interoperability between rail and maritime transport.